A review on probiotics and dietary bioactives: Insights on metabolic well-being, gut microbiota, and inflammatory responses - Alice Njolke Mafe; Great Iruoghene Edo; Osamah S. Majeed; Tayser Sumer Gaaz; Patrick Othuke Akpoghelie; Endurance Fegor Isoje; Ufuoma Augustina Igbuku; Joseph Oghenewogaga Owheruo; Rapheal Ajiri Opiti; Yasal Garba; Arthur Efeoghene Athan Essaghah; Dina S. Ahmed; et al. (Food Chemistry Advances)
This review explores the impact of probiotics and dietary bioactives on gut microbiota, inflammatory responses, and metabolic well-being. It emphasizes how these bioactive components, particularly probiotics, influence gut health by modulating the gut microbiota, a vital ecosystem of microorganisms that play a key role in health. The paper investigates the mechanisms through which probiotics and bioactives, found in both traditional and contemporary foods, support gut health and combat metabolic disorders. It highlights the various types of probiotics in foods, their effects on immune function, and their role in regulating inflammatory response and metabolic well-being. By examining the connections between probiotics, gut microbiota, and outcomes such as digestive health, immune function, and metabolic well-being, this review identifies conditions where probiotics show potential benefits. It also addresses hurdles, including variability in strain effectiveness and dosage, and outlines future research areas, particularly personalized probiotic approaches. The paper concludes with a summary of key insights, underscoring the importance of probiotics and dietary bioactives in food systems to improve health and prevent metabolic diseases.